The house, the world, and the theatre : self-fashioning and authorial spaces in the prefaces of Hawthorne, Dickens, and James /: self-fashioning and authorial spaces in the prefaces of Hawthorne, Dickens, and James. (2016) - Cáffaro, Geraldo
No abstract available